Hind limb ossification centre hypoplasia and deformities induced by quadriceps contracture: Radiographic and Computed Tomographic study in 13 Doberman Pinscher littermates. (March 2021) - Andreis, Maria Elena; Polito, Umberto; Modina, Silvia Clotilde; Carnevale, Liliana Maria; Veronesi, Maria Cristina; Di Giancamillo, Alessia; Roccabianca, Paola; Di Giancamillo, Mauro
Abstract: Quadriceps contracture (QC) is reported in dogs mainly as a complication of trauma or parasitic infection. QC causes progressive hind limb deviation, muscular hypotrophy and degenerative joint disease and, in puppies, bone hypoplasia. The aim of this clinical case series is to describe the radiographic and computed tomographic (CT) changes in hind limb ossification centres in thirteen 55 to 57-days-old Doberman Pinscher related littermates induced by QC after repeated intramuscular injections. The presence, size, and shape of ossification centres of affected and unaffected hind limbs were compared. Affected limbs were hyperextended and externally rotated, with genu recurvatum and proximo-medial patellar luxation. QC had no influence on the time of appearance of ossification centres however, it was associated with femoral head flattening, hip subluxation, flattening of the femoral distal epiphysis. The tibial plateau was tilted caudoproximally-craniodistally and wedged into the growth plate. Thirty-two out of fifty-five ossification centres (including diaphyseal and epiphyseal centres, such as femoral head and tibial plateau) were significantly smaller in affected limbs ( p < 0.05). Lack of weight-bearing could account for the smaller size of ossification centres in affected tarsi and metatarsi. Progressive limb hyperextension and external rotation might have induced gradual loading withdrawal on the medial aspect of the foot justifying the reduced size observed only for the medial ossification centres of the digits of affected limbs. To the best of our knowledge, this is the first study describing CT findings of hind limb ossification centre changes in puppies with QC contracture. Highlights: A Doberman Pinscher litter developed quadriceps contracture. Pathology did not affect the time of appearance of hindlimb ossification centres. Pathology caused hypoplasia and deformation of hindlimb ossification centres. Pathology caused limb deviation, muscle hypotrophy and degenerative joint disease.